Odonata (Insecta) community in the Environmental Protection Area of the Machado River hydrographic basin, southern Minas Gerais State, Brazil - Guedes, Marcella Bigoni; Vilela, Diogo Silva; Souza, Marcos Magalhães de (Papéis Avulsos de Zoologia, 2022)
Only 8% of the approximately 120 conservation units in Minas Gerais State collect information on the order Odonata, which motivated this study. We aimed to survey communities of this insect group in the Environmental Protection Area of the Machado River hydrographic basin, southern Minas Gerais State, Brazil. For this purpose, 12 areas were sampled by active searching from September 2018 to March 2019. Representatives of 71 Odonata species belonging to 8 families were collected. Seven species were found exclusively in this conservation unit, and two species were newly recorded for the state, namely Erythrodiplax chromoptera (Borror, 1942) and Micrathyria venezuelae De Marmels, 1989. This study surveyed the fifth richest odonatofauna in Minas Gerais State, underscoring the importance of the studied area for conservation of Odonata communities and necessitating actions for decreasing environmental impacts on this biological patrimony.